Les hésitations de la parole autorisée durant la crise de la zone euro - Philippe Légé; Jaime Marques Pereira (Revue de la Régulation)
In this paper, the evolution of the dominant discourses on the Eurozone crisis is analyzed. The hypothesis of a crisis of these discourses due to their incapacity to deliver a credible vision about on the recovery of growth is advanced. We attribute this incapacity to a cognitive path-dependence, leading to conceive the way out of the crisis by means of a new “governance” supposed to guarantee at last budgetary rigor and structural reforms. The analysis of the evolution of the discourses reveals that this inertia of the doctrine implied a sequence of stutterings in the “authoritative statements” issued by policy-makers. The crisis brought continuing denials of the discourses held by decision-makers. The sequence of theses denials produced first a cognitive dissonance followed by two major controversies on the appropriate rhythm of budgetary consolidation and on the right extension of unconventional monetary policy. Despite partial revisions of these judgments, these controversies are still going on and numerous uncertainties are subsisting. Therefore, in addition to its properly economic dimension, the Eurozone crisis is also a crisis of the persuasion capacity of authoritative statements from Governments, Central Banks and economists.